α thalassaemia in British people - Higgs, DR; Ayyub, H; Clegg, J; Hill, A; Nicholls, R; Teal, H; Wainscoat, J; Weatherall, D (1985)
Although α thalassaemia is rare in north Europeans, it has been identified in British people with no known foreign ancestry. Twelve such patients were studied, of whom eight shared a distinctive molecular defect, which was clearly different from defects seen in subjects of Mediterranean or South East Asian origin. A rare but specific form of α thalassaemia is therefore present in the British population. In addition, two patients from families of mixed racial origin were encountered who had a moderately severe form of thalassaemia (HbH disease) due to the inheritance of one form of α thalassaemia from the British parent and another type from the foreign parent. This shows the importance of careful genetic counselling of British patients with haematological findings of thalassaemia.